Tall Fescue Performance under Low Maintenance Conditions in the National Turfgrass Evaluation Program Test - Jack D. Fry (Kansas Agricultural Experiment Station Research Reports, 2022)
The National Turfgrass Evaluation Program (NTEP) Tall Fescue Test was planted in 2018 at the Kansas State University Olathe Horticulture Center, Olathe, KS. Differences have been observed among entries maintained under low maintenance conditions.
Keywords: tall fescue; low input; drought; turf quality